Updated social accounting matrices for Malawi and Rwanda - CGIAR Research Program on Policies, Institutions, and Markets (2018)
The SAM for Malawi was used in the Malawi National Investment Plan 2017/18-2022/23. The SAM for Rwanda was used in Rwanda's Strategic Plan for Agriculture Transformation 2018-24.